Studi Optimasi Parameter Daya RF untuk Penumbuhan Lapisan Tipis Mikrokristal Silikon dengan Metode Hot Wire Cell PECVD - S. Amiruddin; L. Usman; Mursal Mursal; T. Winata; Sukirno Sukirno (Institute for Research and Community Services (LPPM) ITB, 2005)
The Hot Wire Cell PECVD method has been developed and successfully applied to grow the hydrogenated amorphous silicon (a-Si:H) thin films with a relatively high conductivity. The a-Si:H thin films were grown on the 7059 corning glass at a filament temperature of 800 oC. Ten percents silane (SiH4) gas diluted in hydrogen (H2) gas was used as gas source. In the hot wire cell PECVD method, reactant gases are decomposed as a result of reaction with a heated filament. The filament was placed parallelly with inlet gas system and outside of electrodes. The characterization results exhibited that the deposition rate increased from 1.02 Ã…/s to 1.90 Ã…/s with increasing the rf power from 80 watt to 120 watt. The optical bandgap decreased from 1.65 eV to 1.56 eV with increasing the rf power from 80 watt to 120 watt. The SEM image and the XRD spectrum exhibited the transition of amorphous to microcrystalline silicon at an rf power of 120 watt. The transition of amorphous to microcrystalline was indicated by the reduction of amorphous parts and the appearance of peak diffraction at <111> preferential crystal orientation. The dark and photo conductivities of the obtained Î¼c-Si:H thin films was 6.84x10-6 S cm-1 and 4.16x10-4 S cm-1, respectively.